Only one-third of hepatocellular carcinoma cases are diagnosed via screening or surveillance: a systematic review and meta-analysis. Issue 3 (March 2020) - Zhao, Changqing; Xing, Feng; Yeo, Yee Hui; Jin, Michelle; Le, Richard; Le, Michael; Jin, Mingjuan; Henry, Linda; Cheung, Ramsey; Nguyen, Mindie H.
Abstract : Background/objects: Early hepatocellular carcinoma diagnosis is associated with better long-term survival. Studies of at-risk patients who are monitored in routine practice have reported an overall adherence rate to hepatocellular carcinoma screening/surveillance of approximately 60% and suboptimal diagnostic efficacy of the current screening/surveillance tools. However, it is unclear how many hepatocellular carcinoma patients were actually diagnosed via screening/surveillance given these obstacles. Therefore, via a systematic review of PubMed and Scopus databases from 2000 to 2019, we aimed to identify the proportion of patients with hepatocellular carcinoma diagnosed via screening/surveillance in routine practice. Methods: We included original research articles of studies of patients already diagnosed with hepatocellular carcinoma that reported the proportion of hepatocellular carcinoma diagnosed via screening/surveillance. Results: The study included 60 studies and 50 554 hepatocellular carcinoma cases. The pooled proportion of hepatocellular carcinoma diagnosed by screening/surveillance was 37% (95% confidence interval: 31%–44%) and differed by geographic region (North America/Asia/Europe/Oceania/Africa/South America, 31%/42%/41%/30%/29%/47%, P = 0.017, respectively) and by surveillance interval (<12 months 39% vs. 12 months 19%, P < 0.01) but not by disease etiology, cirrhosis status, clinical setting, practice setting, hepatocellular carcinoma diagnosis period, or surveillance method. Conclusion: Globally, hepatocellular carcinoma was diagnosed via screening/surveillance in less than half of the patients (37%) regardless of healthcare setting or liver disease etiology and without improvement over time despite several recent guideline updates. Research is needed to understand the barriers to screening/surveillance to include medical as well as social and cultural influences. Abstract : Supplemental Digital Content is available in the text.